Analisis Hukum Skema Kontrak Gross Split Terhadap Peningkatan Investasi Hulu Minyak Dan Gas Bumi - Fajri, Muhammad (UI Scholars Hub, 2020)
As a solution to the problems of the Cost Recovery production sharing contract system, the Government of Indonesia through the Ministry of Energy and Mineral Resources issued Minister of Energy and Mineral Resources of the Republic of Indonesia Regulation Number 08 of 2017 concerning Gross Split Production Sharing Contracts. This new regulation is motivated by the low number and length of time of the discovery of oil and gas reserves, along with the Non-Tax State Revenue (PNBP) which continues to decline in the upstream oil and gas sector. The Gross Split profit sharing scheme also offers bureaucratic cuts in investment that are expected to attract investors to carry out exploration and exploitation in Indonesia. This study aims to analyze the legal rules related to Gross Split regulation in the aspect of improving the upstream investment climate of oil and gas and analyze the new role of the Special Oil and Gas Working Unit as an institution appointed by the state to control and supervise the activities of the PSC’s Company in Production Sharing Contract.